The association of visually-assessed quality of movement during jump-landing with ankle dorsiflexion range-of-motion and hip abductor muscle strength among healthy female athletes - Rabin, A.; Einstein, O.; Kozol, Z. (Physical Therapy in Sport, 2018)
Objective: To explore the association between ankle dorsiflexion (DF) range of motion (ROM), and hip abductor muscle strength, to visually-assessed quality of movement during jump-landing. Design: Cross-sectional. Setting: Gymnasium of participating teams. Participants: 37 female volleyball players. Main outcome measures: Quality of movement in the frontal-plane, sagittal-plane, and overall (both planes) was visually rated as "good/moderate" or "poor". Weight-bearing Ankle DF ROM and hip abductor muscle strength were compared between participants with differing quality of movement. Results: Weight-bearing DF ROM on both sides was decreased among participants with "poor" sagittal-plane quality of movement (dominant side: 50.8° versus 43.6°, P=.02; non-dominant side: 54.6° versus 45.9°, P=.01), as well as among participants with an overall "poor" quality of movement (dominant side: 51.8° versus 44.0°, P<.01; non-dominant side: 56.5° versus 45.1°, P<.01). Weight-bearing ankle DF on the non-dominant side was decreased among participants with a "poor" frontal-plane quality of movement (53.9° versus 46.0°, P=.02). No differences in hip abductor muscle strength were noted between participants with differing quality of movement. Conclusions: Visual assessment of jump-landing can detect differences in quality of movement that are associated with ankle DF ROM. Clinicians observing a poor quality of movement may wish to assess ankle DF ROM.